Synthesis and Spectral Characterization of a Thiol-Reactive Long-Lifetime Ru(II) Complex - Terpetschnig, Ewald (Anal Biochem, 1997)
We report the synthesis and spectral properties of a long-lifetime luminescent Ru complex containing a sulfhydryl-reactive maleimide group, [Ru (2,2′-bipyridine)(2)(1,10 - phenanthroline - 5 - maleimide)](PF(6))(2). [Ru(bpy)(2)(phen-mi)](2+) was covalently linked to human serum albumin, immunoglobulin G, and β-galactosidase. The lifetimes for probe bound to proteins were near 1.1 μs. In the absence of rotational motions, the probe displayed an anisotropy near 0.17 for excitation near 475 nm. Anisotropy decay data were used to determine rotational correlation times of the proteins, which showed local probe motions in addition to overall rotational diffusion. This long-lifetime sulfhydryl-reactive probe can be used to recover microsecond rotational motions and/or domain motions of proteins and/or macromolecular complexes.